Family Caregivers in Rural Uganda: The Hidden Reality - Kipp, Walter; Tindyebwa, Denis; Rubaale, Tom; Karamagi, Ednah; Bajenja, Ellen (Health Care for Women International, 2007)
Kabarole, Kyenyoyo, and Kamwenge districts have a home-based care program that consists of formal and informal parts. The formal part is made up of professional, government-paid nurses who are based at the nearest health center and who visit the homes of patients who have been admitted to the program. The informal part of the program is composed of family members who are the principle caregivers for the AIDS patients at home. Home care nurses deal only with the care for the AIDS patients and not with personal issues of the family caregiver. In the past few years, home visits of professional nurses have declined due to funding shortages of the Kabarole Health Department. Before funding cuts were introduced, the home-based care program coverage reached only an estimated 35% of homes requiring care. The HIV prevalence in the sexually active population is high and estimated to be around 14% in the districts. An estimated 4,200 AIDS patients require clinical care in the Kabarole district alone. The districts are typical for sub-Saharan Africa, with a high burden of infectious diseases, including malaria, tuberculosis, and parasitic infections. All homes visited during this study had no running water and no electricity, and were built poorly, with thatched roofs, mud walls, and earthen floors. Generally, home-based care programs are very much limited in Uganda and, to the best of our knowledge, there was no information on any formal programs targeting family caregiver support.
Keywords: Family Caregivers; Rural Uganda; Hidden Reality